Development of an instrument for risk factors of ERP implementation in Indian manufacturing sector. (12th January 2022) - Sar, Archana; Garg, Poonam
In a competitive manufacturing sector, many organisations have chosen to adopt enterprise resource planning (ERP) system to improve the business benefits but ERP implementation involves high risk and is expensive and complex. This research conceptualises and develops an instrument for analysing the risk factors of ERP implementation in the Indian manufacturing sector. For this study, confirmatory factor analysis (CFA) has been employed to analyse composite reliability (CR), convergent validity, and goodness of fit for the individual constructs and measurement models. This study has empirically identified and verified four dimensions of risks related to ERP implementation, which are human risk, managerial risk, technical risk, and organisational risk and found that these factors contribute to 72.64% of the associated risks. For the implementers, this study acts as an important tool that supports risk identification at the initial stage for managing and ensuring that the benefits of ERP are captured and the risks are mitigated.